Characteristics and Indications of Legal Abortion among the Pregnant Women in Lorestan Province of Iran during 2017–2019 - Zahra Fatemi; Soheila Akbari (Advances in Public Health)
Background. Legal abortion is a challenge from the viewpoint of ethics and religion. The present study was conducted to investigate the frequency of fetal and maternal indications of legal abortion and also the maternal characteristics in Lorestan Province of Iran. Methods. As a descriptive cross-sectional study, all the cases with issued permits for legal abortion were selected by a census during 2017–2019. Descriptive data analysis was used to report the results. Event rates with Poisson 95% confidence intervals (CIs) were calculated based on the regional population. Results. A total of 305 cases were selected. The mean age of the mothers was 31.61 ± 7.48 years, and the mean of gestational age was 15.76 ± 2.80 weeks. Demographically, most cases were from Khorramabad city (101 cases) followed by Borujerd (51 cases) and Doroud (46 cases). The overall event rate was 1.732 per 10,000 individuals (95% CI: 1.543–1.938) of the general population of the region per 3 years. Fetal disturbance of the brain and spine was the most prevalent reason of abortion (24.92%, 95% CI: 19.63%–31.19%) followed by Down syndrome (19.34%, 95% CI: 14.73%–24.95), hydrops fetalis (12.79%, 95% CI: 9.09%–17.48%), and anencephaly (12.79%, 95% CI: 9.09%–17.48%). Conclusion. From each 10,000 individuals of the population, one to two cases of legal abortion were screened per 3 years. More than 90% of cases had fetal indication. In cities with lower event rates, we should plan for better screening.